2015
DOI: 10.1080/10408398.2013.858235
|View full text |Cite
|
Sign up to set email alerts
|

Spice use in food: Properties and benefits

Abstract: Spices are parts of plants that due to their properties are used as colorants, preservatives or medicine. The uses of spices have been known since long time, and the interest in the potential of spices is remarkable due to the chemical compounds contained in spices, such as phenylpropanoids, terpenes, flavonoids and anthocyanins. Spices, such as cumin (cuminaldehyde), clove (eugenol) and cinnamon (cinnamaldehyde) among others, are known and studied for their antimicrobial and antioxidant properties due to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(68 citation statements)
references
References 66 publications
2
53
0
1
Order By: Relevance
“…[44] Application of cinnamon in food Antimicrobial activity Recent studies have shown that cinnamon can prevent microorganism-induced food spoilage. [66] Anti-bacterial activity, particularly against Bacillus subtilis, Staphylococcus aureus, Bacillus cereus, Escherichia coli, Salmonella typhi, and Pseudomonas aeruginosa, as well as antifungal activity, mainly against Aspergillus (A. niger, A. flavus, A. ochraceus, and A. terreus), Fusarium (F. graminearum and F. moniliforme), and Penicillium (P. citrinum and P. viridicatum), have been demonstrated. [22,67] C. zeylanicum essential oil at a concentration of 500 ppm has been reported to inhibit the growth of some species of Streptococcus, Enterococus, Acinetobacter, Enterobacter, Klebsiella, Proteus, Mycobacterium, Clostridium, Listeria, and Candida.…”
Section: Anti-hypertriglyceridemiamentioning
confidence: 99%
“…[44] Application of cinnamon in food Antimicrobial activity Recent studies have shown that cinnamon can prevent microorganism-induced food spoilage. [66] Anti-bacterial activity, particularly against Bacillus subtilis, Staphylococcus aureus, Bacillus cereus, Escherichia coli, Salmonella typhi, and Pseudomonas aeruginosa, as well as antifungal activity, mainly against Aspergillus (A. niger, A. flavus, A. ochraceus, and A. terreus), Fusarium (F. graminearum and F. moniliforme), and Penicillium (P. citrinum and P. viridicatum), have been demonstrated. [22,67] C. zeylanicum essential oil at a concentration of 500 ppm has been reported to inhibit the growth of some species of Streptococcus, Enterococus, Acinetobacter, Enterobacter, Klebsiella, Proteus, Mycobacterium, Clostridium, Listeria, and Candida.…”
Section: Anti-hypertriglyceridemiamentioning
confidence: 99%
“…Therefore, the application of clove and its most important medicinal composition eugenol (C10H12O2, CAS No. : 97-53-0) in food industry as antiseptic attracts many attentions of researchers recently (Hu, Gerhard, Upadhyaya, Venkitanarayanan, & Luo, 2016;Patel, 2015;Jessica Elizabeth et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Plant parts are used as spice like leaves (mint, rosemary), flower (clove), bulb (garlic, onion) and fruit (cumin, red chilli). They enjoy the status of GRAS [79]. Factors that affect the antimicrobial efficacy of a compound incorporate target microorganism, initial microflora of the food and environmental factors.…”
Section: Plant Extractsmentioning
confidence: 99%
“…The plants that possess antioxidant property which belong to Lamiaceae, rosemary, oregano, thyme, sage, marjoram, basil, coriander and pimento are predominant [79]. Lipid peroxidation is the main culprit in the rejection of meat and meat products.…”
Section: Plant Extractsmentioning
confidence: 99%